Mitochondrial dynamics in cisplatin resistance: molecular mechanisms and therapeutic targeting - Huang, Wei; Sun, Wei; Yang, Zhiyuan; Li, Yiwen; Wang, Ziliang (Frontiers in Oncology, 2026)
Cisplatin remains a cornerstone of chemotherapy for numerous cancers, despite the persistent challenges of toxicity and the development of drug resistance. Therefore, a deeper understanding of the mechanisms behind cisplatin resistance and the development of strategies to counter it are of critical importance. This review systematically examines the pivotal role of mitochondrial dynamics in cisplatin resistance and discusses emerging therapeutic strategies that target these processes. Mitochondrial dynamics regulate the structure and function of the mitochondrial network through a balance of fusion and fission. Dysregulation of this process directly contributes to cisplatin resistance by maintaining cellular energy homeostasis, inhibiting apoptosis, and enhancing oxidative phosphorylation (OXPHOS). Furthermore, mitophagy, metabolic reprogramming, and the tumor immune microenvironment converge on mitochondrial dynamics to drive the acquisition of drug resistance. Consequently, targeting mitochondrial dynamics presents a promising approach to overcome cisplatin resistance. Potential strategies include restoring the balance of fusion and fission, intervening in mitophagy, disrupting OXPHOS metabolism, and developing mitochondrial-targeted nanodrug delivery systems. However, despite this promising outlook, significant challenges remain, including the heterogeneity of resistance mechanisms, a lack of reliable biomarkers, and the need for selective targeting to minimize off-target effects.